Penambahan Tepung Protein Kedelai Sebagai Pengikat Pada Sosis Sapi - Sofiana, Anjar (Fakultas Peternakan Universitas Jambi, 2012)
The aim of this research was to observe influence of soy concentrate addition as binder to sausage toward pH value, water holding capacity, cooking loss, dan emulsion stability. The experiment used a randomized block design with 5 levels 0, 5, 10, 15, and 20% soy concentrate with 4 repetitions included on the block. The data were analyzed by Analysis of Variance and Duncan’s Multiple Range Test. The result showed that there were no significant (P>0,05) on pH value, water holding capacity of sousage, and cooking loss, but there was significant (P<0,05) on emulsion stability. In conclusion, soy concentrate can be used up to 20% on beef sausage.